Application Strategy Islamic Jariyah management based on Al-Syariah Maqoshid in BMTS - Maziyah Mazza Basyah, Siti Nur Indah Rofiqoh, Syamsir Alamsyah, (Opción, 2019)
The purpose of this paper is to understand the strategy to practice Islamic Jariyah management based on Maqoshid Al-Sharia principle of BMTs via Analytical Hierarchy Process (AHP) method. As a result, a competent human resource in BMTs is the main strategy of Islamic application of the management of Maqoshid Al-Syariah. Based on observation in cooperative-BMT, it can be concluded that Islamic Jariyah management strategic in cooperative-BMT based on Maqosid Syariah can be held by three alternatives.